Peran Akuntansi Digital dan Literasi Digital Dalam Pengembangan Usaha Mikro, Kecil dan Menengah (UMKM) Rumah Makan Sinar Mulya - NURAINI; Alqorni, Nisa; Putri, Femitri Eka (Jurnal Manajemen Dan Akuntansi Medan, 2025)
Sinar Mulya Restaurant is one of the Micro, Small, and Medium Enterprises (MSMEs) engaged in the food and beverage service sector in Pekanbaru City. In today’s digital era, the ability of business owners to manage finances efficiently through digital accounting and to understand technology is a crucial factor in enhancing competitiveness. This study aims to analyze the role of digital accounting and digital literacy in the development of MSME Sinar Mulya Restaurant in Pekanbaru. This research uses a qualitative method with data collection techniques through interviews and literature review. The results show that the implementation of digital accounting can simplify transaction recording, financial reporting, and improve the accuracy and reliability of financial information. Meanwhile, digital literacy skills help optimize the use of technology in business operations. However, challenges such as limited technological understanding and lack of training remain major obstacles in the digital transformation process of MSMEs.